2021
DOI: 10.1039/d1ra04351j
|View full text |Cite
|
Sign up to set email alerts
|

Cyan color-emitting nitrogen-functionalized carbon nanodots (NFCNDs) from Indigofera tinctoria and their catalytic reduction of organic dyes and fluorescent ink applications

Abstract: The present study reports the synthesis of nitrogen-functionalized carbon nanodots (NFCNDs) by a low-cost hydrothermal method using the leaf extract of Indigofera tinctoria as a novel carbon precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The adsorption peak of C. quadrangularis stem extract showed up at 266 nm, indicating the π–π* transition of polyphenols in the extract. 55 The peak appearing around 271 nm is related to the π–π* transition of aromatic conjugated C=C, and the shoulder peak at 310 nm is due to the C=O chromophore of different functional groups in the structure of the N-CDs. 56 The inset figure shows the blue luminescence of synthesized N-CDs when they are irradiated under UV–vis light at 365 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption peak of C. quadrangularis stem extract showed up at 266 nm, indicating the π–π* transition of polyphenols in the extract. 55 The peak appearing around 271 nm is related to the π–π* transition of aromatic conjugated C=C, and the shoulder peak at 310 nm is due to the C=O chromophore of different functional groups in the structure of the N-CDs. 56 The inset figure shows the blue luminescence of synthesized N-CDs when they are irradiated under UV–vis light at 365 nm.…”
Section: Resultsmentioning
confidence: 99%
“… where and are the quantum yields for N-CDs and quinine sulphate, while and stand for fluorescence emission intensities of the reference and sample, respectively, , is the measured absorbance, and denotes the refractive index of the solvent used. 55 …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, increasing awareness on green chemistry and other biological processes has led to the development of an ecofriendly approach for the synthesis of carbon dots from plants rich in carbon content. 23,24 Lourenco et al constructed manganese-doped cobaltite using the zeolitic-imidazolate framework 67 (ZIF-67) as a template, which gives an overpotential of 338 mV at 10 mA/cm 2 . 25 Yang et al reported Co and Fe-codoped CDs, a novel electrocatalyst, which showed a lower overpotential of 308 mV at 10 mA/cm 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Teak is also used for many folklore medicines and treating inflammatory swelling, and extract from various parts of the teak shows a healing capacity for biliousness, bronchitis, hyperacidity, diabetes, leprosy, astringent, and dysentery. Nowadays, increasing awareness on green chemistry and other biological processes has led to the development of an eco-friendly approach for the synthesis of carbon dots from plants rich in carbon content. , Lourenço et al constructed manganese-doped cobaltite using the zeolitic-imidazolate framework 67 (ZIF-67) as a template, which gives an overpotential of 338 mV at 10 mA/cm 2 . Yang et al reported Co and Fe-codoped CDs, a novel electrocatalyst, which showed a lower overpotential of 308 mV at 10 mA/cm 2 …”
Section: Introductionmentioning
confidence: 99%